Peasant Strategies in Revolutionary Mexico. Smallholding and Construction of Empowerment in the Villages of Natívitas (Tlaxcala 1856-1921) - Sanchez, Evelyne (Revista Complutense de Historia de América, 2013)
This study intends to analyze the restructuring of the local authorities in the Natívitas Valley, Tlaxcala, from the 1870’s to the 1920’s through a micro-analytical approach that favors two original axes: the definition of the categories handled by actors, which have been taken from the study of their social experience and, at the same time, the analysis of their use within the context of revolutionary strategies. This text is composed of two parts, in which methodological reflections and case studies are presented. The first section of the study presents a balance of the local powers in the second half of the 19th century and a description of how the peasants began to build their strategic resources against the landowners. Then, the text discusses how the smallholdings and their related categories were resources that could be successfully mobilized by the peasants in the agrarian struggles of the Revolution.